BURNOUT AMONG HOSPITAL EMPLOYEES: THE CASE OF DUZCE AND SAKARYA (Third Sector Social Economic Review, 2018)
The main aim of this study is to determine the hospital employees’ burnout level and explain the differences among employess’ burnout level according to demographic variables. In this study, “Maslach Burnout Inventory” which is developed by Maslach and Jackson (1986) and which adaptation to Turkish is made by Ergin (1992) is used to measure burnout level of employees. The sample of the study consists of totally 122 hospital employees working in Duzce and Sakarya. %77,9 of the participants were female and the emotional exhaustion score of female was higher than male. Emotional exhaustion scores of unmarried participants were higher than married ones. The findings of this study showed that emotional exhaustion scores were higher among the employess who are nurse and health officers.
Keywords: Burnout; Emotional Exhaustion; Hospital Employees; Health Sector; Organizational Behavior